Process Of Reform. A View From The Teaching Personnel Of De University Of Nayarit. - Navarro Hernandez, Maria del Refugio; Ladron de Guevara, Lourdes C. Pacheco; Romo Gonzalez, Prisca Icela; Hernandez Cueto, Carmen (European Scientific Journal, ESJ, 2016)
The university, as an institution, takes a long time to change, since its change does not happen as it does with organisms that transform completely. Rather, what characterizes universities is their resistance to change, their adaptation, counterproposals and negotiations (Porter 2003, Ibarra 2005, 2006), which are expressed with unique characteristics in each particular case. The apparent contradictions, in a complex and hard to unravel context, are that motivate this study. We ask whether such changes will create a new university or will lead it into an undesirable road; whether the university is able to defend its original goals. Can it experience transformation with the same strength and creativity today as with that was found in the collective conscience forty years ago? Can it maintain its spirit of commitment with its social, cultural, and ecological environment? Can it conserve its â€œsense of selfâ€? In order to understand how the essence of the university ethos is maintained or altered, â€œA university with sense of selfâ€ shows the ideas, attitudes, experiences and interpretations of the main actors at the Universidad AutÃ³noma de Nayarit, the professors how they face these changes, and the â€œinstitutional reformâ€ being proposed. We seek to explain how anticipated and desired change by the broader community in Nayarit, is in fact understood, assumed, lived, and carried out.